Molecular determinants of Ca(2+) sensitivity at the intersubunit interface of the BK channel gating ring - Li, Qin (Sci Rep, 2018)
The large-conductance calcium-activated K(+) (BK) channel contains two intracellular tandem Ca(2+)-sensing RCK domains (RCK1 and RCK2), which tetramerize into a Ca(2+) gating ring that regulates channel opening by conformational expansion in response to Ca(2+) binding. Interestingly, the gating ring’s intersubunit assembly interface harbors the RCK2 Ca(2+)-binding site, known as the Ca(2+) bowl. The gating ring’s assembly interface is made in part by intersubunit coordination of a Ca(2+) ion between the Ca(2+) bowl and an RCK1 Asn residue, N449, and by apparent intersubunit electrostatic interactions between E955 in RCK2 and R786 and R790 in the RCK2 of the adjacent subunit. To understand the role of the intersubunit assembly interface in Ca(2+) gating, we performed mutational analyses of these putative interacting residues in human BK channels. We found that N449, despite its role in Ca(2+) coordination, does not set the channel’s Ca(2+) sensitivity, whereas E955 is a determinant of Ca(2+) sensitivity, likely through intersubunit electrostatic interactions. Our findings provide evidence that the intersubunit assembly interface contains molecular determinants of Ca(2+)-sensitivity in BK channels.